DIGITALISASI PRASARANA DESA MAMPUN BARU MELALUI QR CODE LOKASI DAN BUKU TAMU DIGITAL - Widia Putri Febriani; Nabila Sasgita; Habibi; Rizki Apriadi Bahari; Puryanti; Nesha Kosela (AbdiMasya | Hira Institute, 2026)
Digitizing village services is one effort to improve administrative effectiveness and ease public access to information. This community service activity aims to implement digitalization of Mampun Baru Village infrastructure through location QR codes and a digital guest book. The methods used included surveys, preparation, outreach, training, and mentoring with a demonstrative and interactive approach through presentations, discussions, hands-on practice, and questions and answers. The results of the activity showed that QR codes were successfully implemented on various village infrastructure, allowing residents and visitors to quickly access location information via Google Maps. In addition, the digital guest book was able to replace the manual recording system, making administrative processes more efficient, well-documented, and easier to manage. The training provided also improved the knowledge and skills of village officials in operating both systems independently. This program has made a positive contribution to improving the quality of public services, administrative efficiency, and supporting the transformation of Mampun Baru Village towards more modern, information technology-based governance.